Independent and combined impact of texture manipulation on oral processing behaviours among faster and slower eaters. Issue 18 (26th August 2022) - Janani, R.; Tan, Vicki Wei Kee; Goh, Ai Ting; Choy, Michelle Jie Ying; Lim, Amanda JiaYing; Teo, Pey Sze; Stieger, Markus; Forde, Ciarán G.
Abstract : Food texture combinations have a stronger impact in moderating oral processing behaviours and eating rate (g min −1 ), than individual texture changes. This effect was the same for faster and slower eaters. Abstract : Background : Food texture can moderate eating rate and ad libitum energy intake. Many foods are combined with condiments when consumed and the texture and eating properties differ considerably between condiments and carrier foods. Little is known about how combinations of textures impact oral processing or whether these differences are affected by individual eating-styles. Objective : We investigated the impact of texture parameters (unit size, thickness, hardness and lubrication) on oral processing behaviours for carrots and rice-crackers, and tested whether these behaviours differ between 'faster' and 'slower' eaters. Method : Seventy participants (34 males, 26.0 ± 5.4 years, BMI = 21.5 ± 1.7 kg m −2 ) consumed 24 weight-matched carrot samples varying in unit size (large/medium/small), thickness (thick/thin), hardness (hard/soft) and lubrication (with/without mayonnaise). In a second step, participants consumed 8 weight-matched cracker samples varying in unit size (large/small), hardness (hard/soft) and lubrication (with/without mayonnaise). Sample consumption was video-recorded for post hoc behavioural annotation to derive specific oral processing behaviours. Participants were divided into 'faster' or 'slower' eater groups using a post hoc median split based on eating rate of raw carrot. Results : Across texture parameters, hardness had the largest influence ( p < 0.001) on eating rate for both carrots and crackers. The independent texture differences for carrot ranked from most to least impact on eating rate was hardness > thickness > lubrication > unit size. For crackers, the rank order of eating rate was hardness > lubrication > unit size. Harder carrot samples with decreased unit size and reduced thickness combined had a larger synergistic effect in reducing eating rate ( p < 0.001) than manipulation of any single texture parameter alone. Reducing the unit size of crackers while increasing hardness without lubrication combined ( p = 0.015) to produce the largest reduction in eating rate. There were no significant differences between fast and slow eaters on their oral processing behaviours across texture manipulations. Conclusions : Combinations of texture manipulations have the largest impact in moderating oral processing behaviours, and this is consistent across 'faster' and 'slower' eaters. Changing food-texture presents an effective strategy to guide reformulation of product sensory properties to better regulate eating rate and energy intake, regardless of an individual's natural eating-style.